Optimizing tunneling incentive and bonus mechanism: Transfer pricing and tax minimization strategy for corporate sustainability - Nela Nehayati; Yusuf Iskandariah; Enny Susilowati Mardjono (Proceeding International Conference on Accounting and Finance, 2025)
Transfer pricing is still a significant strategic issue, especially in the natural resources sector in Indonesia, which has an impact on state tax revenues and global economic stability. This research aims to analyze the influence of bonus and tunneling incentive mechanisms on transfer pricing decisions, with tax minimization as a moderating variable. The data used is secondary data from natural resource sector companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period, with a total of 166 sample data selected using a purposive sampling technique. Analysis was carried out using WarpPLS 8.0. The research results show that the bonus and tunneling incentive mechanisms do not have a significant effect on transfer pricing decisions, while Tax Minimization can moderate the influence of the bonus and tunneling incentive mechanisms on transfer pricing. The implications of this research emphasize that companies need to pay attention to tax minimization strategies that are in accordance with applicable regulations to avoid prolonged tax conflicts and disputes. In this case, the Tax Authority is also expected to carry out regular regulatory reviews to monitor opportunities for manipulation that can be carried out.